1980
DOI: 10.1136/bmj.280.6226.1253
|View full text |Cite
|
Sign up to set email alerts
|

Community study of hypothyroidism in Down's syndrome.

Abstract: 1253 siderable hazard.4 5 It must be carefully monitored and clotting factors and platelet concentrates given as soon as they are indicated. '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 5 publications
0
16
2
Order By: Relevance
“…Our finding of hypothyroidism (15%) in patients with Down's syndrome is comparable with the prevalence rates of The age distribution of hypothyroidism cases is shown in Table-III. [15][16][17][18][19] The variation in prevalence in these earlier studies might be related to the age variation among the studied subjects and/or to differences in diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Our finding of hypothyroidism (15%) in patients with Down's syndrome is comparable with the prevalence rates of The age distribution of hypothyroidism cases is shown in Table-III. [15][16][17][18][19] The variation in prevalence in these earlier studies might be related to the age variation among the studied subjects and/or to differences in diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Comparison with other reports is difficult, as prevalence will vary according to the age of the population tested and the type and degree of thyroid dysfunction measured [9]. For example, Lobo et al [13] reported gross hypothyroidism (TSH ≥23 mU/l) in 3/83 subjects (3.6%) with DS aged 5–21 years, whereas Tuysuz and Beker [14] found raised TSH in 90/320 patients with DS aged between 5 days and 10 years, of whom 9 had transient, congenital or acquired hypothyroidism and 81 (25.3% of the total) had compensated hypothyroidism (TSH 6–20 mU/l).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a high incidence of acquired hypothyroidism in children with Down syndrome [8,9,11].…”
Section: Introductionmentioning
confidence: 99%